THE EFFECTIVENESS OF TAX INCENTIVE POLICIES IN SUPPORTING THE AVAILABILITY OF DRUG AND HEALTH DEVICES IN DUREN PALM HEALTH CENTER - Rulandari, Novianita (Jurnal Pendidikan Sosiologi dan Humaniora, 2022)
This study aims to analyze the effectiveness of incentives, efforts and tax barriers in supporting the availability of medicines and medical devices in handling Covid-19 at the Duren Sawit District Health Center. Data was collected through face-to-face interviews with each research subject. The research method used is a qualitative approach by adopting the theory of Merilee S. Grindle. The results of the study show that the Tax Incentive Policy has been well implemented to support the availability of medicines and medical devices in handling Covid-19 at the Duren Sawit District Health Center. However, this policy has not fully impacted the availability of the desired medicines and medical devices, due to several obstacles that have arisen from both the public and government sides as policy makers. These obstacles caused the community's economic recovery process during the pandemic era to not be optimal, and the realization of the tax incentives achieved was also not optimal. To overcome these obstacles, thorough supervision from the tax authorities is required regarding the implementation of this tax incentive. In addition, socialization activities are needed for the general public regarding tax incentives and their application. Puskesmas also need to plan program target strategies, such as prioritizing integration in service delivery and utilizing information and communication technology. The Ministry of Finance needs to focus more on optimizing the absorption of existing tax incentives.